2004
DOI: 10.1007/s00737-003-0038-0
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum depression: in relation to life events and patterns of coping

Abstract: The purpose of this study was to estimate the prevalence of postpartum depression (PPD) and its relationship with life events (LE) and patterns for coping. We performed a cross-sectional study of 113 women, on the 10(th) day of puerperium, at the Obstetric Clinic of the São Paulo University Medical School. The study was based on the following: Pitt (1967) and Stein (1980) Scales, Beck Depression Inventory (1961), Holmes and Rahe Schedule of Recent Events (1967), Folkman and Lazarus Ways of Coping (1985) and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
21

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 52 publications
2
50
0
21
Order By: Relevance
“…26,27 There was also mixed evidence regarding the relationship between CPMD and the number of living children in a woman's care. While three studies 22,38,45 found higher prevalence of CPMDs among women who had three or more children other studies found no association between family size and mental health. 18,31,32 …”
Section: Family and Social Relationshipsmentioning
confidence: 89%
See 2 more Smart Citations
“…26,27 There was also mixed evidence regarding the relationship between CPMD and the number of living children in a woman's care. While three studies 22,38,45 found higher prevalence of CPMDs among women who had three or more children other studies found no association between family size and mental health. 18,31,32 …”
Section: Family and Social Relationshipsmentioning
confidence: 89%
“…Rates of CPMD were also higher among women who were young 9,37,49 ; of a religious minority, 34 or unmarried. 13,39,55 However, other studies found no association between CPMD and maternal age 10,13,16,20,22,32,36,45,48 ; marital status 9,34,37,47 ; economic difficulties or a low income 13,22,26,32,36,45,48 ; unemployment 9,16,26,34,36,47 or adverse life events. 10,31…”
Section: Systematic Reviewsmentioning
confidence: 94%
See 1 more Smart Citation
“…Dez estudos estimaram a prevalência da DPP no Brasil 22,[29][30][31][32][33][34][35][36][37] . Foram encontradas taxas de 7,2% a 43%.…”
Section: Depressão Pós-parto (Dpp)unclassified
“…Quanto mais grave e persistente for a 36 João Pessoa -PB 21 202 2ª semana ao 12°mês EPDS > 11 Moraes et al 33 Pelotas -RS 19 410 30º ao 45º dia Escala de Depressão de Hamilton > 17 Faisal-Cury et al 35 São Paulo -SP 16 113 10º dia Beck Depression Inventory Cantilino et al 37 Recife -PE 16 120 2ª a 26ª semana PDSS > 102…”
Section: Depressão Pós-parto (Dpp)unclassified